Seni Membaca Pikiran: Rahasia Mengelola SDM - Hanif Yanuar; Adi Lukman Nurhakim; Agung Purwanto; Iza Aulia Rahmawati; Muhammad Ainul Yaqin (Yayasan Aya Sophia Indonesia, 2024)
The purpose of reviewing this book is so that the author can understand the contents of the book published by Hijaz Pustaka Mandiri with the author Windri Maharani which is entitled The Art of Reading the Powerful Secret Thoughts of Successful People and can be applied directly in everyday life because in this book there are so many benefits that can be taken. The method used in this study is a qualitative method. Quaitative research is research that produces and processes descriptive data, such as book reviews. It is said to be qualitative because basically this research aims to examine or research an object in a natural setting without any manipulation in it, and the expected results are not based on quantitative measures, but rather the meaning or terms of the contents of the book being observed.